2018
DOI: 10.1007/s12028-018-0512-1
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Near-Infrared Spectroscopy in Adult Patients Undergoing Veno-Arterial Extracorporeal Membrane Oxygenation

Abstract: Monitoring of rSO could be considered as an interesting tool to monitor the brain of patients on VA-ECMO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 26 publications
1
49
2
1
Order By: Relevance
“…Cerebral near-infrared spectroscopy (NIRS) is a noninvasive monitoring technique that can provide continuous value of forehead regional oxygen tissue saturation, which represents the balance between cerebral oxygen delivery and cerebral oxygen consumption. A recent study reported the association between cerebral desaturation on NIRS with acute brain injury and mortality in VA-ECMO patients (41). NIRS could be an interesting and simple monitoring tool, introducing new therapeutic goals in VA-ECMO patients.…”
Section: Neurological Complicationsmentioning
confidence: 99%
“…Cerebral near-infrared spectroscopy (NIRS) is a noninvasive monitoring technique that can provide continuous value of forehead regional oxygen tissue saturation, which represents the balance between cerebral oxygen delivery and cerebral oxygen consumption. A recent study reported the association between cerebral desaturation on NIRS with acute brain injury and mortality in VA-ECMO patients (41). NIRS could be an interesting and simple monitoring tool, introducing new therapeutic goals in VA-ECMO patients.…”
Section: Neurological Complicationsmentioning
confidence: 99%
“…It can suggest a difference in the cerebral perfusion. A low near-infrared-spectroscopy is associated with a rapid onset poor outcome (risk of cerebral oedema development) and might be used to guide treatment in patients undergoing ECMO [142].…”
Section: Electroencephalogrammentioning
confidence: 99%
“…However, a study by Zahraa found that there was no difference in central nervous system complications between pediatric respiratory failure patients supported on VA versus VV ECMO [20]. Differential hypoxia, where the arterial oxygen tension is lower in the upper half of the body than in the lower half, is a phenomenon occasionally seen in patients supported on peripheral VA ECMO that causes cerebral ischemia [21]. For pediatric patients on VA ECMO, the incidence of stroke was much lower for transthoracic or central cannulation compared to peripheral cannulation [22].…”
Section: Veno-arterial (Va) Versus Veno-venous (Vv)mentioning
confidence: 99%
“…When the probe is placed on the forehead, it measures cerebral oximetry. An analysis of adult patients on VA ECMO showed that cerebral desaturation was common and mortality higher for patients with cerebral desaturation compared to those without [21]. A sudden decrease in cerebral saturation can be associated with an acute neurological event, prompting further investigation.…”
Section: Cerebral Near Infra-red Spectroscopy (Nirs)mentioning
confidence: 99%